Equivalent Static Wind Loads: Recent developments and analysis of a suspended roof. (1st October 2017) - Patruno, L.; Ricci, M.; de Miranda, S.; Ubertini, F.
Highlights: Equivalent Static Wind Loads are reformulated in order to take into account the contemporaneity between effects. The procedure is extremely efficient and does not require computationally intense Monte Carlo optimizations. The proposed procedure is tested on a large span suspended roof. Abstract: Equivalent Static Wind Loads (ESWLs) represent an extremely useful tool for the characterization of the structural response to the wind action and provide a convenient way for structural engineers in order to include the results of a complete, rigorous, buffeting analysis in the design process. Recently, a novel approach to the determination of ESWLs has been proposed which is based on the adoption of Proper Skin Modes for the characterization of the static/quasi-static structural response. In that study, the reconstruction of the extreme internal forces over the structure for all structural members has been performed in a least square sense and a smoothed version of the maximum/minimum operators, typical of envelope calculations, has been adopted. By using such formulation, it is possible to use efficient, gradient-based, optimization techniques in the minimization procedure which leads to the identification of ESWLs. In this paper, two refinements of the original technique are proposed: the least square approach is modified in order to ensure a complete covering of the envelope and the original formulation is extended in order to take into consideration the contemporaneity between effects. Finally, the proposed approach is tested on a large span suspended roof derived from the structural model of the New Juventus Stadium showing extremely encouraging results.